EXTH-33. VALPROIC ACID ENHANCES THE ANTI-PROLIFERATIVE EFFECT OF TUMOR-TREATING FIELDS ON PATIENT-DERIVED GLIOSARCOMA CELLS IN VITRO. (9th November 2020) - Michelhaugh, Sharon; Mittal, Sandeep
Abstract: BACKGROUND: Valproic acid (VPA) is an anti-epileptic drug often prescribed for glioma-associated seizures. VPA is also investigated as a potential anti-proliferative cancer treatment due to its histone deacetylase inhibitor activity. Tumor-treating fields (TTFields) are an FDA-approved therapy that reduce proliferation of tumor cells by interfering with microtubule formation during mitosis. In this study, we determined whether the combination of VPA with TTFields in comparison to each treatment alone would alter proliferation or cytotoxicity in patient-derived gliosarcoma cells. METHODS: Gliosarcoma cells were grown in DMEM/F12 media with 10% fetal bovine serum and gentamicin. Prior to TTFields application and VPA incubation, cells were plated on plastic coverslips (1×10 4 cells/coverslip) and incubated overnight. TTFields were applied to cells at 200 kHz optimal frequency (field intensity of ~1.6 V/cm) for 14 days and/or incubated with VPA at concentrations of 0, 0.25, 0.5, or 1mM. Proliferation was assessed by quantifying total RNA from each coverslip (n=3–4/group). Cytotoxicity was assessed by measuring lactate dehydrogenase (LDH) released into the media (n=8/group). Groups were compared by t-tests. RESULTS: RNA yields from cells treated with only VPA were unchanged compared to control. TTFields treatment alone reduced RNA yield from 14.85±4.23 to 8.92±1.39 µg (mean± SD; P < 0.05). The addition of 1mM VPA to TTFields further reduced RNA yield to 5.48±1.5 µg ( P < 0.03), although VPA alone had no effect. Additionally, 1mM VPA increased media LDH from 4.00±1.3 to 6.68±1.7 AU (mean± SD; P < 0.01), while TTFields alone also increased media LDH to 5.67±0.99 AU ( P < 0.02). Media LDH levels due to combined TTFields and 1mM VPA treatment was 5.86±1.2 AU (not statistically different from either alone). CONCLUSIONS: In patient-derived gliosarcoma cells, TTFields and VPA individually elicited modest cytotoxicity. However, TTFields plus VPA combination treatment reduced proliferation more than TTFields alone, though VPA treatment alone did not induce an anti-proliferative effect.